Applications of functional data analysis in sport biomechanics - Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
This paper reconsiders the challenge of analysing coordination in human movement with particular emphasis on the application of Functional Data Analysis and Functional Principal Component Analysis. The process of Functional Data Analysis is outlined using examples from biomechanics of sports injuries and coordination in race-walking, jumping and running. The evolution of the spring mass model used to describe jumping and hopping behaviour is examined and it is proposed that this model represents a coordination structure in human movement which may be appropriately analysed using Functional Data Analysis methods.